Developing The Application Wordbuddy - Practicing English Speaking With Ai Support - Luong, Thi Nhu Y (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Software Engineering; 2020 - 2025